Actividades lúdicas y la comunicación oral en niños de la Institución Educativa Inicial N° 847 Nuestra Señora de la Purísima, Punchana 2024 - Salvino Jean, Jany Yolina (2025)
The research was to determine the relationship between the application of recreational activities and the development of oral communication in children with the purpose of the Initial Educational Institution No. 847 Nuestra Señora de la Purísima, located in Punchana, during the year 2024. The focus of the The research was quantitative, relational, with a correlational and transectional design. The study sample consisted of 99 boys and girls between the ages of 3 and 5, enrolled in the selected educational institution. To collect the information, the observation technique was applied, using a specially designed guide that was validated by three experts in the field. The statistical analysis produced a value of tc = 8.878, derived from a correlation coefficient of rs = 0.722, which demonstrates a positive relationship of moderate to high level between the analyzed variables. Based on these results, the null hypothesis is rejected, and the general hypothesis is accepted, confirming that the implementation of play based activities has a significant relationship with the development of children’s oral communication.